Doing Qualitative Research / A Practical Handbook - Silverman David (Sage Publications, 2005)
A Gem of this book! This is the perfect primer for novice researchers. What You Can Do With Qualitative Research, The Research Experience 1, The Research Experience 2, What Counts as ''Originality''?, Starting Out, Selecting a Topic, Using Theories, Choosing a Methodology, Selecting a Case, Writing a Research Proposal, Analyzing Your Data, Beginning Data Analysis, Developing Data Analysis, Quality in Qualitative Research, Evaluating Qualitative Research, Keeping in Touch, Keeping a Record, Relations in the Field, Getting Feedback, Writing Up, The First Few Pages, The Literature Review Chapter, The Methodology Chapter, Writing Your Data Chapters, The Final Chapter, The PhD Examination, Surviving .a PhD Oral, Review, Effective Qualitative Research, The Aftermath, Getting Published, Audiences, Finding a Job, Glossary, References, Author and Subject Index.